2-Aminoethoxydiphenylborane is an acute inhibitor of directly photosensitive retinal ganglion cell activity in vitro and in vivo. - Sekaran, S; Lall, G; Ralphs, K; Wolstenholme, A; Lucas, R; Foster, R; Hankins, M (2007)
The mammalian retina contains directly photosensitive retinal ganglion cells (RGCs), which use the photopigment melanopsin. The generation of mice lacking melanopsin has been invaluable in elucidating the function of these cells. These animals display deficiencies in circadian photoentrainment, the pupil light reflex, and the circadian regulation of the cone pathway. Interpreting the results from such gene knock-out models is always complicated by neuronal plasticity and the potential for restructuring of neuronal networks. Until now, the study of photosensitive RGCs has lacked an acute inhibitor. 2-Aminoethoxydiphenylborane (2-APB) is an antagonist at IP3 receptors and an inhibitor of canonical transient receptor potential ion channels (TRPCs). Here, we show that 2-APB is an extremely potent in vitro inhibitor of the photosensitive RGCs and that its effect is independent of store-dependent Ca2+ release. The identification of canonical TRPC6 and TRPC7 ion channels in melanopsin-expressing ganglion cells suggests that 2-APB may act directly on a TRPC ion channel. Importantly, using the pupil light reflex as a functional assay, we show that 2-APB inhibits photosensitive RGC activity in vivo. Collectively, our data further elucidate the phototransduction pathway in the photosensitive RGCs and demonstrate that 2-APB can be used to silence activity in these cells both in vitro and in vivo.